Hubungan Kadar CO Udara dengan Kadar Karboksihemoglobin Pada Pedagang Kaki Lima Sekitar Traffic Light - Rizaldi, Muhammad Addin; Ma’rufi, Isa; Ellyke, Ellyke (Jurnal Kesehatan Lingkungan Indonesia, 2021)
Latar belakang: Paparan karbon Monoksida dapat menyebabkan keracunan yang dapat mmembentuk karboksihemoglobin (COHb) dalam darah. Penelitian ini bertujuan untuk mengetahui hubungan kadar CO Udara dengan Kadar COHb pada pedagang kaki lima.Metode: Jenis penelitian ini adalah analitik observasional dengan pendekatan kuantitatif dan rancangan studi cross sectional. Sampel yang diambil berjumlah 28 pedagang kaki lima. Pengambilan sampel pada penelitian ini menggunakan Teknik Purposive Sampling. Pengujian kadar COHb dilakukan menggunakan spektofotometri yang dilakukan di Laboratoriaum Biokimia Fakultas Kedokteran Universitas Jember. Pengambilan sampel udara dilakukan menggunakan alat CO Monitor. Analisis yang dilakukan dalam penelitian ini uji korelasi spearmen dan Chi Square.Hasil:  Hasil pada penelitian ini diketahui bahwa ada beberapa titik yang memiliki kadar CO udara diatas baku mutu yaitu pada pagi hari di traffic light Jalan Gajah Mada serta pada pagi dan malam hari di traffic light Jalan Basuki Rahmat. Berdasarkan hasil analisis terdapat hubungan antara faktor individu merokok (p=0,0001) dan umur (p=0,030) dengan kadar COHb dalam darah. Variabel yang tidak berhubungan adalah kadar CO Udara (p=0,376) dan keluhan kesehatan.Simpulan: Masih ada kadar CO udara diatas baku mutu, terdapat hubungan antara faktor individu umur dan merokok dengan peningkatan kadar COHb. ABSTRACT Title: Relationship of Cabon Monoxide Levels with Carboxyhemoglobyn Levels in Street Vendor around Traffic Light Basuki Rahmat Street and Gajah Mada Street Jember RegencyBackground: Carbon monoxide exposure can cause poisoning which can form carboxyhemoglobin (COHb) in the blood. This study aims to determine the relationship between air CO levels and COHb levels in street vendors.Method: This type of research is an observational analytic with a quantitative approach and a cross sectional study design. Samples taken amounted to 28 street vendors. Sampling in this study using purposive sampling technique. Testing of Carboxyhemoglobyn was carried out using spectophotometry which was carried out at the Biochemistry Laboratory of the Faculty of Medicine, University of Jember. Air sampling was carried out using a CO Monitor tool. The analysis conducted in this study was the spearmen correlation test and Chi Square.Result: The results of this study show that there are several points that have carbon monoxide levels above the quality standard. Based on the results of the Chi Square test, it is known that there is a relationship between individual smoking factors (p = 0.0001) and age (p = 0.030) with COHb levels. Unrelated variables were air CO levels (p = 0.376) and health complaints. Conclusion: There are still carbon monoxide levels that are above the quality standard, there is a relationship between individual age factors and smoking with an increase in COHb levels.ABSTRACT Title: Relationship of Cabon Monoxide Levels with Carboxyhemoglobyn Levels in Street Vendor around Traffic Light Basuki Rahmat Street and Gajah Mada Street Jember RegencyBackground:Carbon monoxide exposure can cause poisoning which can form carboxyhemoglobin (COHb) in the blood. This study aims to determine the relationship between air CO levels and COHb levels in street vendors.MethodThis type of research is an observational analytic with a quantitative approach and a cross sectional study design. Samples taken amounted to 28 street vendors. Sampling in this study using purposive sampling technique. Testing of Carboxyhemoglobyn was carried out using spectophotometry which was carried out at the Biochemistry Laboratory of the Faculty of Medicine, University of Jember. Air sampling was carried out using a CO Monitor tool. The analysis conducted in this study was the spearmen correlation test and Chi Square.Result: The results of this study show that there are several points that have carbon monoxide levels above the quality standard. Based on the results of the Chi Square test, it is known that there is a relationship between individual smoking factors (p = 0.0001) and age (p = 0.030) with COHb levels. Unrelated variables were air CO levels (p = 0.376) and health complaints.Conclusion: There are still carbon monoxide levels that are above the quality standard, there is a relationship between individual age factors and smoking with an increase in COHb levels.